If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(8n+2)-8n=32-6n
We simplify the equation to the form, which is simple to understand
-2(8n+2)-8n=32-6n
Reorder the terms in parentheses
+(-16n-4)-8n=32-6n
Remove unnecessary parentheses
-16n-4-8n=+32-6n
We move all terms containing n to the left and all other terms to the right.
-16n-8n+6n=+32+4
We simplify left and right side of the equation.
-18n=+36
We divide both sides of the equation by -18 to get n.
n=-2
| -12m+4=8m-6 | | -2x-15=-(6x+7) | | 2x+x+(j-3)=17 | | 4(y+4)=2(17-2y) | | n-23=5(n-7) | | 9w^2+30w+25=0 | | 0.80(r-100.00)=150.00 | | 6X-48=52+2X | | 48-n=4x*7n | | 6(5n-2)=-39+3n | | 10x+20=12x-4 | | 15=x+1.1 | | 8y-3=5(y-1)Z+3y | | (3x)+y=20 | | -2+8a=2(a-7) | | 6a=2a+1 | | 2x^2+y=18 | | -7x=-8(2x-1)+5x | | 5n-14=1+2n | | 35h+75=180 | | -5-6x=7+4(-8x-3) | | -2w(w-7)(w+8)=0 | | x^2+34x+514=0 | | 7y+8y=y+12 | | 3(3x+3)=-16+4x | | =6y+2x-2y-3x | | 4(y-1)=6y-12 | | 8(5+7x)=5x-11 | | 3*x+1.5*y=3 | | 3x^2+4=-5 | | Y=x^2+37x | | -8a-14=-6(a+4) |